Biocidal (bacterial and cancer cells) activities of chitosan/CuO nanomaterial, synthesized via a green process. (1st May 2021) - Karthikeyan, Chandrasekaran; Varaprasad, Kokkarachedu; Venugopal, Senthil Kumar; Shakila, S.; Venkatraman, B.R.; Sadiku, Rotimi
Graphical abstract: Highlights: Eco-friendly multifunctional CCuO NM was synthesized via the green process. Copper salt was nucleated with Psidium Guajava leaves extract to form the NM CCuO NM exhibits efficient antibacterial and anticancer actions. CCuO NM is suitable for healthcare applications. Abstract: Biopolymer-based nanomaterials have been developed as antimicrobial and anticancer agents due to their advanced physical, chemical and biomedical characteristics. Herein, chitosan-copper oxide nanomaterial was, successfully synthesized by a green method. In this process, copper salt was nucleated with Psidium guajava leaves extract in order to form the nanomaterial in the chitosan network. Attenuated total reflection-fourier transform, infrared spectroscopy, X-ray diffraction, Dynamic light scattering, Transmission electron microscope, Field emission scanning electron microscopy/Energy dispersive X-ray analysis, X-ray photoelectron spectroscopy and Photoluminescence spectroscopy techniques were, employed to characterize the synthesized nanomaterial. The average size of the nanomaterial was identified to be ∼52.49 nm with XRD. The antibacterial study of CCuO NM showed higher activity than the commercial amoxicillin against gram-positive (G + ve) ( Staphylococcus aureus, Bacillus subtilis ) and gram-negative (G-ve) bacteria ( Klebsiella pneumonia, Escherichia coli ). CCuO NM showed in-vitro anticancer potential against human cervical cancer cells (Hela) with an IC50 concentration of 34.69 μg/mL. Photoluminescence spectrum of CCuO NM showed a green emission (oxygen vacancies) observed at ∼516 nm, which is attributed to the generation of reactive oxygen species (ROS) by the nanomaterial, which is believed, to be responsible for the biocidal (cell death) effects. These results suggested that CCuO is a promising nanomaterial that could be suitable for advanced applications in the healthcare industries.